So Rich, So Poor: Household Income and Consumption in Urban Spain in the Early Twentieth Century (Zaragoza, 1924) - Marco-Gracia, Francisco J.; Delgado, Pablo (International review of social history, 2025)
Studies on household income and consumption in Southern Europe have primarily focused on rural areas and factory workers. In this study, we aim to incorporate evidence of household income, considering the earnings of all household members and not just the male wage, using the population list of Zaragoza (Spain) from 1924. This population list is the first (and the last) to systematically record the wages of all citizens regardless of their family role or age. Our results confirm that, in 1924, most working-class households still required the labour of women and/or children to meet basic consumption needs (on average, they contributed nearly sixty per cent of the household income). Based on different food consumption baskets, the results also show that, with household income, the majority of working-class families could afford a basic consumption basket but not a nutritionally more complete basket.